Role of B cells as antigen presenting cells - Rastogi, Ichwaku; Jeon, Donghwan; Moseman, Jena E.; Muralidhar, Anusha; Potluri, Hemanth K.; McNeel, Douglas G. (Frontiers in Immunology, 2022)
B cells have been long studied for their role and function in the humoral immune system. Apart from generating antibodies and an antibody-mediated memory response against pathogens, B cells are also capable of generating cell-mediated immunity. It has been demonstrated by several groups that B cells can activate antigen-specific CD4 and CD8 T cells, and can have regulatory and cytotoxic effects. The function of B cells as professional antigen presenting cells (APCs) to activate T cells has been largely understudied. This, however, requires attention as several recent reports have demonstrated the importance of B cells within the tumor microenvironment, and B cells are increasingly being evaluated as cellular therapies. Antigen presentation through B cells can be through antigen-specific (B cell receptor (BCR) dependent) or antigen non-specific (BCR independent) mechanisms and can be modulated by a variety of intrinsic and external factors. This review will discuss the pathways and mechanisms by which B cells present antigens, and how B cells differ from other professional APCs.